2023
DOI: 10.3389/fpsyt.2023.1122256
|View full text |Cite
|
Sign up to set email alerts
|

Two years COVID-19 pandemic: Development of university students' mental health 2020–2022

Abstract: BackgroundThe literature indicates a negative impact on the mental health of university students during the COVID-19 pandemic. It remains unclear if this negative impact persists even after lockdown measures are lifted. The current study therefore investigates the mental health status of students by drawing on two previous studies the present study seeks to investigate differences in the mental health status across three time points.MethodsA cross-sectional, anonymous online survey among students of six univer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 89 publications
0
15
0
Order By: Relevance
“…Emotions have a profound impact on learning [ 33 ]. Jian Yang et al found that uncertainty about the COVID-19 pandemic and concerns about their own health may increase anxiety and stress among nursing students [ 34 ]. This emotional state may affect their concentration, learning efficiency, and even their performance in the field of education.…”
Section: Discussionmentioning
confidence: 99%
“…Emotions have a profound impact on learning [ 33 ]. Jian Yang et al found that uncertainty about the COVID-19 pandemic and concerns about their own health may increase anxiety and stress among nursing students [ 34 ]. This emotional state may affect their concentration, learning efficiency, and even their performance in the field of education.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, this study aimed to investigate (i) differences between various timepoints of the COVID-19 pandemic (2020, 2021, and 2022) in mental health outcomes and social and emotional aspects in domestic and international students, separately, (ii) differences between international and domestic students between the three timepoints on mental health outcomes and social and emotional aspects, and (iii) possible moderation effects of timepoints on mental health outcomes and social and emotional aspects of domestic and international students. In this study, similarly to Kohls and colleagues [ 18 ], we hypothesized that the levels of depressive symptoms, suicidal thoughts, and loneliness would significantly differ between the three points in time, being more prominent in the 2021 cohort due to prolonged restrictions and long-lasting effects of the COVID-19 pandemic for both domestic and international students. We also hypothesized that the levels of depressive symptoms, suicidal thoughts, and loneliness would be higher among international students compared to domestic students.…”
Section: Introductionmentioning
confidence: 89%
“…During each of the three timepoints, an anonymous online survey was conducted, using similar questionnaires across all timepoints. The results of each cross-sectional study have already been published [ 8 , 9 , 18 ].The questionnaires were offered in German and English due to the large number of international students enrolled at German universities who are not proficient in German. From the existing data, in these studies, we performed a secondary analysis by grouping students who answered the online questionnaires in English as “international students”, and who answered in German as “domestic students”.…”
Section: Methodsmentioning
confidence: 99%
“… Elmer et al (2020) and Conceição et al (2021) reported that the prevalence of anxiety and depression among students from Switzerland and Portugal increased during the early phase of the COVID-19 pandemic as compared to before the pandemic. Furthermore, Kohls et al (2023) found in cross-sectional studies that students reported higher levels of depression in 2021 than in 2020. These trends in mental health justify the application of evidence-based psychological interventions addressing mental health issues and needs among university students.…”
Section: Introductionmentioning
confidence: 98%
“…Several studies have explored the impact of the pandemic on students’ mental health (e.g., Elmer et al, 2020 ; Conceição et al, 2021 ; Karing, 2021 ; Kohls et al, 2023 ). Elmer et al (2020) and Conceição et al (2021) reported that the prevalence of anxiety and depression among students from Switzerland and Portugal increased during the early phase of the COVID-19 pandemic as compared to before the pandemic.…”
Section: Introductionmentioning
confidence: 99%